Making love with the land : essays - Whitehead, Joshua (Writer) (University of Minnesota Press, 2022)
"In prose that is evocative and sensual, unabashedly queer and visceral, raw and autobiographical, Joshua Whitehead writes of an Indigenous body in pain, coping with trauma. Intellectually audacious and emotionally compelling, Whitehead shares his devotion to the world in which we live and brilliantly-even joyfully-maps his experience on the land that has shaped stories, histories, and bodies from time immemorial"--